Form of Local Government Supervision on The Implementation of The Responsibilities of Companies Holding Oil and Gas Business Licenses to The Community - Lakburlawal, Mahritha Aprilya; Haliwela, Nancy Silvana; Pesulima, Theresia Louize (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This community service activity focuses on local government supervision of the implementation of social responsibility of oil and gas companies in East Seram Regency. This area is rich in natural resources, but its management is not optimal and causes socio-environmental conflicts due to weak supervision and the absence of regional regulations governing the implementation and evaluation of corporate CSR.Purposes of The Devotion: This service is carried out in order to provide knowledge and understanding of the form of Local Government Supervision on the implementation of the responsibilities of oil and gas license holders to the community against the Regional Government of East Seram Regency which is a finding in previous research.Method of The Devotion: Community Service (PKM), impact on improving the quality of higher education, as well as the results of PKM will provide legal education for the community. Therefore, community service activities are carried out through legal consultation, it is considered important to do in order to provide understanding and knowledge and legal awareness for the Regional Government of East Seram Regency about the implementation and supervision of the implementation of social responsibility that is integrated and coordinated between OPD related agencies, so that social Responsibility funds from companies are maximized for development in East Seram RegencyResults Main Findings of the Devotion: the absence of supervision from the local government on the implementation of Corporate social Responsibility both by companies holding oil and gas business licenses but also to any company that runs its business in East Seram Regency, because there is no regulation on the basis of the implementation of such supervision at the regional level. The form of integrated supervision between institutions is one of the important indicators that must be regulated in the regulation. The absence of a basis for government action on the implementation of Corporate social Responsibility and coordination between local government organizations led to the results of the implementation of Corporate social Responsibility can not be maximized to support development in the region. This service activity uses the method of legal counseling, where resource persons provide material, then discussions and questions and answers are carried out. This service activity was carried out in East Seram Regency, Maluku province, which involved several related East Seram Regional Government Organizations.